The Immediate Results of Mirtral Valve Repair with Using Artificial Chords in Mitral Prolapse - S. I. Mokhnatiy; L. V. Pidhaina; O. M. Dovgan; O. D. Babliak (Ukrainian Journal of Cardiovascular Surgery, 2016)
This paper presents an analysis of 69 consecutive patients with mitral valve prolapse, which were operated from January 2011 to December 2015 at the UCCC. The MV repair with using artificial chords performed in all patients. Of the 69 patients, the correction was successful in 68 cases (98,5%). 1 (1,5%) patient was reoperated 8 month after first MV repair. There were no incidences of hospital mortality.Using of artificial chords is a obligatory element in MV repair, which enables a high percentage of good immediate postoperative results.